2018
DOI: 10.3390/ijms19113629
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Response Gene to Complement 32 (RGC-32) in Diabetic Mouse Retina Is Involved in Retinopathy Development

Abstract: Diabetic retinopathy (DR) is a severe and recurrent microvascular complication in diabetes. The multifunctional response gene to complement 32 (RGC-32) is involved in the regulation of cell cycle, proliferation, and apoptosis. To investigate the role of RGC-32 in the development of DR, we used human retinal microvascular endothelial cells under high-glucose conditions and type 2 diabetes (T2D) mice (+Leprdb/ + Leprdb, db/db). The results showed that RGC-32 expression increased moderately in human retinal endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
7
1
Order By: Relevance
“…Previous studies have suggested that diabetes-induced structural and functional alterations in photoreceptors may play a role in DR pathogenesis (15,28). Such retinal abnormalities have also been reported in other studies in db/db mice over 8-24 weeks of diabetes (29,30) and our previous study at 32 weeks of age (15).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Previous studies have suggested that diabetes-induced structural and functional alterations in photoreceptors may play a role in DR pathogenesis (15,28). Such retinal abnormalities have also been reported in other studies in db/db mice over 8-24 weeks of diabetes (29,30) and our previous study at 32 weeks of age (15).…”
Section: Discussionsupporting
confidence: 87%
“…The retinal cells were treated with normal (5 mM of D-glucose) or high concentration of Dglucose (25 mM) or osmotic control L-glucose (25 mM) for 48 h. The results showed that the expression levels of ENOX1 slightly increased in cells treated with high concentration of D-glucose compared to cells treated with normal glucose condition, but no significant difference was observed in both cell types ( Figure 1B). db/db T2D mice at 32 weeks of age exhibited features of the early clinical stages of DR, as reported previously (15). We then compared the protein expression levels of ENOX1 in the retina of T2D and of non-diabetic control mice at 32 weeks of age (Figure 2A).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…[8][9][10][11] Extensive researches have shown that RGC-32 induces cell proliferation, differentiation, invasion, migration, epithelial-mesenchymal transition (EMT) occurrence and metabolism. [12][13][14][15][16] A considerable amount of literatures have been published on regulatory effects of RGC-32 in a variety of non-cancerous diseases, concerning vascular diseases, [17][18][19] Alzheimer's Disease, 20 obesity, 21 diabetic retinopathy, 22 autoimmune encephalomyelitis, 23 renal ischemia reperfusion injury, 24 preeclampsia 25 and other non-tumour diseases. In addition to its mediating role in non-cancer, essential roles of it were identified to facilitate the progressions of numerous malignancies, namely ovarian cancer, 26,27 colon cancer, 28,29 prostate cancer, 30 lung cancer, 31,32 breast carcinoma 33 and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%